The effect of retailer awareness, retailer association, retailer perceived quality, and retailer loyalty towards purchase intention - Bheakanti Bias Btari; Rizal Edy Halim; Sumiyarto (Institute for Advanced Science Social, and Sustainable Future, 2023)
Retail developments in Indonesia continue to increase, especially modern retail which has the greatest growth in comparison with traditional retail, especially retail trade of food and beverage categories. One of them developed at this time is 7-Eleven, attended by positioning itself as a convenience store, but also provides some seating and tables inside and outdoors for 24 hours (hybrid convenience stores). With increasing competition in the retail, it is no less important is whether retail brand or brand can affect consumer purchase intention to come to a retail shop. This study aims to analyze the influence of awareness retailers, retailers association, perceived quality retailer, and retailer loyalty towards consumer's purchase intention possessed. Hypothesis testing is done by using Structural Equation Modeling (SEM). The results of testing the hypothesis known that retailer awareness is not proven positive influence on purchase intention. Retailer awareness and retailer association also not proved a positive influence on retailer loyalty. While retailer association, retailer perceived quality and retailer loyalty proven positive effect on the purchase intention. Hypothesis testing results also showed that the retailer perceived quality has a positive effect on the retailer loyalty.